The Historical Regions of Europe: Civilizational Backgrounds and Multiple Routes to Moder - Gerard Delanty (Historicka Sociologie, 2012)
A systematic typology or comparative analysis of European historical regions does not exist and there is relatively little literature on the topic. The argument in this paper is that a six-fold classification is needed to capture the diversity of Europe's historical regions and that these should be seen in terms of different routes to modernity and have broad civilizational backgrounds in common. The forms of modernity that constitute Europe as a world historical region correspond to North Western Europe, Mediterranean Europe, Central Europe, East Central Europe, South Eastern Europe, North Eastern Europe.